15° Premio Lissone Internazionale di Pittura : Aspetti della giovane pittura svedese : 10 scultori italiani d'oggi. - Caramel, Luciano; Cavaliere, Alik; Crispolti, Enrico; Dell'Acqua, Gian Alberto; Gassiot-Talabot, Gérald; Ghinzani, Alberto; Hamilton, Richard; Marotta, Gino; Pirozzi, Giuseppe; Rambelli, Amilcare; Reichardt, Jasia; Spagnulo, Giuseppe; et al. (Lissone : Comunale del Mobile di Lissone, 1967)
Adami, Valerio ; Alleyn, Edmund ; Anzo ; Armengol, Machi Rafael ; Arroyo, Eduardo ; Atila ; Axell, Evelyne ; Backstrom, Holger ; Baj, Enrico ; Bec, Daniel ; Berg, Bertil ; Biasi, Guido ; Boberg, Jörgen ; Boriani, Davide ; Boyle, Mark ; Brynjolf, Jorgen ; Buri, Samuel ; Carroll, Robert ; Caruso, Bruno ; Cavaliere, Alik ; Cerni, Vicente Aguilera ; Colding, Steen ; Collina, Giuliano ; Cotugno, Salvatore ; Crispolti, Enrico ; Csernus, Tibor ; Dlouhy, Bedrich ; Drago ; Dypréau, Jean ; Elias, Etienne ; Equipo Realidad ; Ferrari, Renzo ; Fieschi, Giannetto ; De Filippi, Fernando ; Fogelquist, Jörgen ; França, José-Augusto ; Friberg, Roj ; Gans, Louis ; Gassiot-Talabot, Gérald ; Gastini, Marco ; Ghinzani, Alberto ; Gioli, Paolo ; Gostomski, Zbignew ; Graubner, Gotthard ; Guerreschi, Giuseppe ; Guiotto, Paolo ; Häfner, Thomas ; Hamilton, Richard ; van der Heyden, J.C.J. ; Hillersberg, Lars ; Hilligsoe, Klaus ; Hofmann, Werner ; Hollesch, Carlo ; Huig, Hendricus (Henk) ; Karlmark, Lars ; De Keyser, Raoul ; Klasen, Peter ; Klein, Yves ; Krohg, Morten ; Lakner, Laszlo ; Lecoultre, Jean ; Leonardi, Luciano ; Lind, Folke ; Lucchini, Cesare ; Macréau, Michel ; Magnus, Carl ; Malmedal, Arne ; Margonari, Renzo ; Marotta, Gino ; Mattinen, Seppo ; Mergl, Vaclav ; Mikl, Josef ; Monory, Jacques ; Nespolo, Ugo ; Nilsson, Bert-Johnny ; Notari, Romano ; Oberhuber, Oswald ; Painitz, Hermann ; Pardi, Gianfranco ; Perez, Augosto ; Petersen, Hans Meyer ; Pezzo, Lucio Del ; Philips, Tom ; Pirozzi, Giuseppe ; Pozzati, Concetto ; Rahmberg, Ulf ; Rambelli, Amilcare ; Reichardt, Jasia ; Relyic, Radomir ; Revilla, Carlos ; Rothschild, Henri ; Samuelson, Ulrik ; Sarkis ; Sarnari, Franco ; Schönenberger, Gualtiero ; Sejka, Leonid ; Smejkal, Frantisek ; Somaini, Francesco ; etc.
biografie
Engels
Frans
Italiaans
boek